Catastrophic COVID-19 Second Wave in Aligarh: Lessons learnt - Rahman, Syed Ziaur; Khan, Saif; Shujauddin, - (Bangladesh Journal of Medical Science, 2021)
The second wave of COVID-19 in India showed its devastated effect mainly in April-May 2021 and crumbled the whole health care infrastructure. Demand for medical oxygen was higher during the second wave of COVID-19 pandemic in comparison to the first spell. Three states viz Maharashtra, Uttar Pradesh and Delhi were more severely affected. Aligarh, a small district of around 1.8 million population lies in the state of Uttar Pradesh (UP). The district is famous as ‘Oxford of the East’ due to large number of intellectuals and teachers living and working at Aligarh Muslim University, was obviously not left unsaved in this second wave. The present paper discussed the catastrophic effect of COVID-19 second wave in Aligarh, the possible reasons behind it, preparation for the anticipated third wave and lessons learnt from the past experience. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.140-143